İbazi̇yye’de Ru’yetullah - Ateş, Orhan (Uluslararası Sosyal Bilimler Dergisi, 2017)
This work deals with ru'yetullah in İbadiyye Sect that is applied in Umman now.
Keywords: Coran -- Controverse théologique